2004
DOI: 10.1099/mic.0.26841-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA-containing membrane vesicles of Pseudomonas aeruginosa PAO1 and their genetic transformation potential

Abstract: Natural membrane vesicles (n-MVs) produced by Pseudomonas aeruginosa PAO1 and PAO1 carrying plasmid pAK1900 (p-MVs) were purified and analysed for DNA content. The MVs were isolated by a procedure designed to ensure no cellular contamination from the parent MV-producing cells. Fluorometry analysis revealed that p-MVs were associated with 7?80 ng DNA (20 mg MV protein)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
280
4
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(297 citation statements)
references
References 35 publications
9
280
4
4
Order By: Relevance
“…However, another (non exclusive) possibility to explain the presence of so much 'viral' DNA in samples that do not contain viral particles visible by electron microscopy is that many MVs present in the ocean samples in fact contain viral (or plasmid) DNA instead of bona fide cellular DNA (Figure 1). In agreement with this possibility, it is well known that bacterial and archaeal MVs can be enriched in plasmid and/or viral DNA (Yaron et al, 2000;Renelli et al, 2004;Soler et al, 2011;Gaudin et al, 2014). Yaron et al (2000) first detected phage DNA in MVs produced by Escherichia coli O157:H7.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…However, another (non exclusive) possibility to explain the presence of so much 'viral' DNA in samples that do not contain viral particles visible by electron microscopy is that many MVs present in the ocean samples in fact contain viral (or plasmid) DNA instead of bona fide cellular DNA (Figure 1). In agreement with this possibility, it is well known that bacterial and archaeal MVs can be enriched in plasmid and/or viral DNA (Yaron et al, 2000;Renelli et al, 2004;Soler et al, 2011;Gaudin et al, 2014). Yaron et al (2000) first detected phage DNA in MVs produced by Escherichia coli O157:H7.…”
mentioning
confidence: 59%
“…However, similar to GTA, microbial MVs can be involved in the transfer of genetic material from cell to cell (Renelli et al, 2004;Velimirov and Hagemann, 2011;Gaudin et al, 2013). We have thus suggested that vMVs can serve as vehicles for the intercellular transport of viral genomes thereby facilitating recombination between viral, plasmid and/or cellular chromosomes (Gaudin et al, 2014).…”
mentioning
confidence: 99%
“…In P. aeruginosa, eDNA release depends on quorum sensing (35), and there is evidence to suggest that cell lysis itself may be achieved by prophage induction within a biofilm (38,50), or alternatively, as a consequence of the release of membrane vesicles that contain bacteriolytic activity (51,52) as well as DNA (53). In Streptococcus mutans and Streptococcus pneumoniae, DNA is released from a lysing subfraction of the bacterial population in response to competence development, a physiological process that also depends on quorum sensing (54)(55)(56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…Their diverse biological functions have been extensively documented (see Table 1). The list of functions attributed to EMVs includes binding and delivery of nucleic acids, transport of virulence factors, ridding the cell of toxic envelope proteins and tumorigenesis (Deich & Hoyer 1982;Dorward et al 1989;Kadurugamuwa & Beveridge 1997;Kesty et al 2004;Renelli et al 2004;McBroom & Kuehn 2007;Valadi et al 2007;Soler et al 2008;Aldick et al 2009;Ellis & Kuehn 2010;Camussi et al 2011;Rak & Guha 2012;Gaudin et al 2013).…”
mentioning
confidence: 99%